THE ROLE OF TEACHER'S GESTURE IN THE CLASSROOM (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the role of teacher's gestures as a crucial component of classroom communication and pedagogical effectiveness. The research analyzes how teachers use various types of gestures to enhance instruction, manage classroom dynamics, and facilitate student comprehension across different educational contexts. The paper investigates the relationship between gestural communication and learning outcomes, exploring how nonverbal behaviors complement verbal instruction to create more effective teaching environments.